The legal aspect of illicit enrichment in Malaysia: Is it a crime to be rich? - Muhammad Azman Ng, Noratikah; Ayub, Zainal Amin; Abdul Rahman, Rohana (UUM Press, 2022)
The growth of illicit enrichment crime or living beyond one’s means is a significant challenge in combating corruption. Many countries have shown their commitment towards preventing illicit enrichment crimes by criminalising and penalising illicit enrichment in their laws, including Hong Kong and Singapore. Illicit enrichment is a crime and Malaysia has no clear provisions on illicit enrichment to prevent it. Therefore, this paper analysed the adequacy of Section 36 of the Malaysian Anti-Corruption Commission Act 2009 [Act 694] (MACC Act 2009). The legal framework on illicit enrichment in Hong Kong and Singapore were referred as sources of critique. To achieve the said objective, this study adopted a doctrinal approach using qualitative research methodology. The scope of the paper is limited due to the inadequacy and indirectness of the law on illicit enrichment in Malaysia. This paper critically analysed the international framework of illicit enrichment and conducted a comparative analysis of the law in Hong Kong and Singapore, namely the Prevention of Bribery Ordinance and the Prevention of Corruption Act 1960, respectively. In conclusion, this paper found that the current law in Malaysia is inadequate and Malaysia can learn to adopt the said laws as provided in Hong Kong and Singapore. This study serves as a guide for legislators intending to address the current inadequacies of the law on corruption in Malaysia, equipped with better knowledge on the characteristics of illicit enrichment. Suggestions to address the issues are proposed.